If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -5y + z = -5 Solving 2x + -5y + z = -5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5y' to each side of the equation. 2x + -5y + 5y + z = -5 + 5y Combine like terms: -5y + 5y = 0 2x + 0 + z = -5 + 5y 2x + z = -5 + 5y Add '-1z' to each side of the equation. 2x + z + -1z = -5 + 5y + -1z Combine like terms: z + -1z = 0 2x + 0 = -5 + 5y + -1z 2x = -5 + 5y + -1z Divide each side by '2'. x = -2.5 + 2.5y + -0.5z Simplifying x = -2.5 + 2.5y + -0.5z
| 17w-9w=32 | | -4x-6(-4x+17)=-282 | | x^2+y^2-8x-2y-6=0 | | 3x-9=f(12) | | -0.7=3k+6 | | 2x+12=4x-76 | | 7/8x-3=4 | | 6x+10=6x+5 | | 7x+6(-5x-6)=-13 | | 13x+6.00=97 | | -4x-(-4x+17)=-282 | | 12x+8=15.5-6 | | (6+6i)x=-3-3i | | 155+x=40 | | 4/5n=18 | | 10x+0.15x=14.50 | | -14x^4-36x^2+54=0 | | 39x=155 | | 1=m-0.9 | | 45x=168 | | 14p+(-8)=22+20p | | (2n+0.5)n=1 | | 154x=40 | | x^2+8x-884=0 | | 4/9x-8-1/3x | | 155x=40+x | | (3x-5)*(x^2-6x+4)= | | 6x+6=4x+28 | | 4/3x-17-5/9x=11 | | 8.4=1.2x-1.2 | | 6*5-n+5*-n+1= | | w=2l+2w+p |